Antlion allometry suggests a greater importance of prey capture among first larval instars. Issue 6 (2nd November 2021) - Farji-Brener, Alejandro G.; Juncosa-Polzella, Agostina S.; Madrigal-Tejada, Daniela; Centeno-Alvarado, Diego; Hernández-Soto, Mariana; Soto-Huaira, Mayori; Gutiérrez-Cruz, Sebastián
Abstract : First larval stages require adequate feeding to reach subsequent instars. However, the accumulation of reserves is also important in the last larval instar because it is vital to pupate and successfully perform metamorphosis into adulthood. We indirectly determined the presence of changes in the relative importance of prey capture through larval ontogeny in the antlion larvae (Neuroptera Myrmeleontidae), a sit-and-wait predator with three instar stages that capture preys that fall into their pit-traps. We used scaling relationships between the size of body parts directly related to prey capture (prothorax) versus those that are not (thorax + abdomen). The prothorax (neck, head, and mandibles) is used in the pit building, prey capture, and re-capture, and pit cleaning. We measured the body parts of 70 larvae of Myrmeleon crudelis in a tropical rain forest of Costa Rica. The prothorax showed negative allometry: it was proportionally larger in the first than in the last instars. These results support the growth hypothesis, which states that food acquisition is key in the earlier stages of larval development. First instars can be more food-limited than later instars because they build small pit-traps where only very small arthropods can fall; have smaller mandibles and relatively lower grab force, increasing the probability of the prey escaping; and have smaller fat reserves and thus, are unable to resist long periods of starvation. This illustrates the relevance of using scaling relationships to better understand how ecological pressures change along ontogeny, emphasizing the role of food acquisition at earlier ontogenetic stages